PENGARUH KOMITE AUDIT, KOMISARIS INDEPENDEN, DAN PROFITABILITAS TERHADAP PENGHINDARAN PAJAK PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2018-2020 - Michaelsan Michaelsan; Yuniarwati Yuniarwati (Fakultas Ekonomi, Universitas Tarumanagara, 2023)
The audit committee is a committee created by the board of commissioners whose task is to carry out inspections or research deemed necessary on the implementation of the functions of the board of directors in managing the company. The audit committee is an important component that must exist in companies listed on the Indonesia Stock Exchange, therefore the Indonesia Stock Exchange requires to form and have an audit committee chaired by an independent commissioner. The existence of an audit committee is expected to improve the quality of internal control which is ultimately intended to provide protection to shareholders and other stakeholders. This study aims to analyze and prove the effect of the audit committee, the influence of independent commissioners, and the influence of profitability on tax avoidance. The sample selection in this study used a purposive sampling method, which is a sampling method, in which samples taken from the population must meet the criteria in accordance with the objectives or research problems. The results of this study are the audit committee has a negative effect on acceptable tax avoidance. Independent commissioners have a negative effect on acceptable tax avoidance. Profitability has a positive effect on tax avoidance rejected.